Management Decisions to Improve Formation and Implementation of the Strategy for the Development of Foreign Economic Relations between Ukraine and Lybia - BULAKHТ.; PLAKHOTNIKOVA, L.; TARASENKOА. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
Libya is an important trade partner of Ukraine in North Africa. A priority objective for Ukraine in the cooperation with Libya is to diversify energy supplies, whereas Libya shows interest to imports of Ukrainian goods and science & technology services. Studies of performance and trends in foreign economic relations of Ukraine with Libya are, therefore, supposed to enhance the effectiveness of foreign economic policy decisions. A statistical analysis for the period of 2008–2018 is made using time series on the foreign trade turnover of goods and services between Ukraine and Libya, bilateral trade in goods, bilateral trade in services, the structure of Ukrainian exports of goods to Libya (2018), and the structure of Ukrainian imports of goods from Libya (2018). The data on the structure of the Ukrainian export and import transactions with Libya show that the Ukrainian exports are dominated by agricultural goods, by far and large food products and crops in particular (more than 80% of the total exports), which can caused by nature conditions of the African continent. The remaining share of Ukrainian exports consists of processed raw materials, ferrous metals (nearly 15% of the total exports) and non-ferrous metals, products of oil refinery, chemical products, machinery and equipment, textiles, leather, footwear, foods and beverages etc. The trade balance is positive for Ukraine. Factors hampering the expansion of trade between the two countries are identified: lack of a basic strategy for foreign trade with Libya, lack of a clear strategic vision of the trade cooperation with Libya, heavy political and economic pressures by the Russian Federation, low quality of normative documents for support and promotion of foreign economic interests etc. Management solutions are proposed to improve formation and implementation of the strategy for the development of foreign economic relations between Ukraine and Libya.